2015
DOI: 10.1542/peds.2015-1260
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Interventions Among Underage Drinkers in the ED: A Randomized Controlled Trial

Abstract: OBJECTIVES: This study examined the efficacy of emergency department (ED)-based brief interventions (BIs), delivered by a computer or therapist, with and without a post-ED session, on alcohol consumption and consequences over 12 months. METHODS:Patients (ages 14-20 years) screening positive for risky drinking were randomized to: BI (n = 277), therapist BI (n = 278), or control (n = 281). After the 3-month follow-up, participants were randomized to receive a post-ED BI session or control. Incorporating motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 73 publications
3
102
4
Order By: Relevance
“…20, 21 Compared with the control condition, we found that both a therapist BI and computer BI significantly reduced alcohol consumption at 3 months and alcohol-related consequences at 3 months and 12 months. 17,18 …”
Section: Introductionmentioning
confidence: 71%
“…20, 21 Compared with the control condition, we found that both a therapist BI and computer BI significantly reduced alcohol consumption at 3 months and alcohol-related consequences at 3 months and 12 months. 17,18 …”
Section: Introductionmentioning
confidence: 71%
“…The ED also has a high level of staff expertise who are well placed to initiate safeguarding procedures where required and who provide a good point of onward referral to specialist services. The possibility of conducting alcohol screening among adolescents presenting at the ED in England should be investigated, and the potential for providing interventions to help reduce alcohol consumption in this population and setting established [15,39].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [34] did not focus on substance use outcomes—despite its testing of a substance abuse prevention program. As a consequence, five studies [27, 46, 51, 52, 54] remain that experienced attrition of 35% or less, that reported at least 1-year behavioral outcomes in substance use, and that favored youths who received the tested computer-based intervention. If the 26 studies considered for this review typify current work, research on computer-based approaches to substance use prevention and intervention among youth will advance slowly.…”
Section: Methodological Issues In Computer-based Programsmentioning
confidence: 99%
“…Ten of the programs evaluated in the 26 studies engaged adults to a lesser or greater extent to deliver computer-based programming. Those adults were professionals, including nurses ( n = 1) [29], school staff and parents ( n = 1) [33], teachers ( n = 4) [34, 35, 38, 39], therapists ( n = 3) [46, 49, 50, 51], and mothers ( n = 1) [52]. A range of formats are extant in the field of computer-based programs to reduce substance use among youth.…”
Section: Computer-based Program Delivery and Venuesmentioning
confidence: 99%
See 1 more Smart Citation